Professional Training in English Language (Hydrocarbons Transportation and Storage). Part 3 электронный курс - Shadrina, A. V. specialist in the field of oil and gas business Professor of Tomsk Polytechnic University, Doctor of Technical Sciences 1980- (TPU Moodle, 2022)
When student successfully complete this course, he/she will be prepared to: list the various technologies and equipment; know the basic principles of technological process regarding safety of oil and gas pipelines; explain the structure of basic principles of technological process; analyze factors influencing the pipeline safety; discuss professional topics in group; demonstrate basic communication skills by working in pairs and small group.